Tourism theory : concepts, models and systems - Lohmann, Gui, 1973- (CABI, 2017)
Developed from the Portuguese textbook Teoria do Turismo, the present book provides thorough coverage of all aspects of tourism theory for students and researchers of tourism. This work has an intermediate structure between that of an encyclopaedia and that of a traditional book. It is organized into 59 entries, which are divided into five sections. The first section presents concepts that are directly related to tourism, including hospitality, leisure, events and entertainment. The second section discusses the relationship between tourism and some of the disciplines that provide the most knowledge to the field, such as philosophy and ethics, anthropology, sociology and culture. Furthermore, it presents fundamental areas of study, including marketing, sustainability, the tourism cluster and the tourism satellite account. The third section addresses aspects of tourists themselves, such as tourism experience, demand and various approaches that classify types of tourists and their behaviours, such as those proposed by John Urry and Stanley Plog. The fourth section involves the elements that connect the origin to the tourism destination, including the distribution channels of tourism products, tourist travel and the travel patterns adopted. The fifth section presents the tourism destination, focusing on aspects of tourism development, supply and infrastructure, along with other phenomena such as image, tourism bodies and seasonality. Author, place and subject indexes can be found at the end of the book.